Exploring Irrigation Futures: Developments in Demand Forecasting. (June 2015) - Weatherhead, Keith; Knox, Jerry; Hess, Tim; Daccache, Andre
Estimates of the magnitude and location of future irrigation demand are essential for strategic planning of water resources at national and regional levels. However, demand forecasting is fraught with difficulty, as water use for supplementary irrigation is highly sensitive to changes in agro-economic policy, climate and future water resources availability. Short-term forecasts are normally based on existing trends, modified by any expected variations. Following a long period of growth, the volume of water being abstracted for irrigation in England and Wales appears to be in decline. After allowing for annual weather variations, the underlying decline in dry year demand was −1.4% per annum from 1990 to 2010. Extrapolating these trends forward suggests a further reduction of around one-quarter (−25%) by 2030. However longer-term forecasts (to the 2050s) need to consider alternative possible futures. The authors used a combination methodology to incorporate changes in population demographics, consumption and consumer preferences under a range of socioeconomic policies for four defined socioeconomic futures. The projected changes in 'unconstrained' demand in a dry year ranged from +40% to +167% by the 2050s; 'actual' water use will be constrained by water availability and allocation policy, which itself may lead to a relocation of demand. Combined with a probable decline in low-flow (summer) water availability, this indicates major future water resource issues. The figures need to be interpreted with caution as they are sensitive to model input values, and ignore impacts of step-change genetic improvements and the effects of changing CO2 concentrations on crop growth. The differences between forecasts also highlight the sensitivity to assumptions and the potential impact of deeper-seated changes on current trends. Some policy options and potential adaptations are discussed.